Cosmetic Pterygium Surgery: Techniques and Long-Term Outcomes - Gulani AC (Dove Medical Press, 2020)
Arun C Gulani, Aaishwariya A Gulani Gulani Vision Institute, Jacksonville, FL, USACorrespondence: Arun C GulaniGulani Vision Institute, 8075 Gate Parkway West Suite 102, Jacksonville, FL 32216, USATel +1 904 296 7393Fax +1888 650-0744Email gulanivision@gulani.comBackground: To demonstrate the long-term results of enhanced cosmetic pterygium surgery with extensive Tenonectomy, adjunctive fibrin-glued amniotic membrane transplantation (AMT), and mitomycin C (MMC).Methods: Retrospective chart review of patients who had pterygium surgery with AMT and MMC between January 2001 to July 2017 and had completed at least 6 months of follow-up. Early and long-term postoperative cosmetic outcomes, recurrence rate, and complications were analyzed. Cosmetic outcomes were evaluated based on patient and surgeon reported outcome measures.Results: The study was conducted on a total of 603 eyes of 578 patients (316 males, 262 females) with an average age of 52.9 ± 15.1 years. At post-op day 1, patients reported no discomfort and could not tell which eye had surgery based on patient reported subjective grading scales. Over an average follow-up period of 23.1 ± 35 months (range: 6– 216 months), there was one pterygium recurrence (0.2%), eighteen granulomas (2.9%), one self-resolving scleral melt (0.2%), one correctable restricted ocular motility (0.2%), one pupil abnormality (0.2%), one dellen (0.2%) and one correctable upper lid abnormality (0.2%). Planned laser vision correction was used for residual corneal scar in eleven eyes (1.8%) as a staged refractive approach.Conclusion: This study highlights an improved technique of an old concept of pterygium surgery that not only reduces the recurrence but also enhances cosmetic excellence and improves the quality of vision.Keywords: amniotic membrane, mitomycin C, pterygium